Near-Infrared Fluorescence Imaging and Photodynamic Therapy for Liver Tumors - Kaibori, Masaki; Kosaka, Hisashi; Matsui, Kosuke; Ishizaki, Morihiko; Matsushima, Hideyuki; Tsuda, Takumi; Hishikawa, Hidehiko; Okumura, Tadayoshi; Sekimoto, Mitsugu (Frontiers in Oncology, 2021)
Surgery with fluorescence equipment has improved to treat the malignant viscera, including hepatobiliary and pancreatic neoplasms. In both open and minimally invasive surgeries, optical imaging using near-infrared (NIR) fluorescence is used to assess anatomy and function in real time. Here, we review a variety of publications related to clinical applications of NIR fluorescence imaging in liver surgery. We have developed a novel nanoparticle (indocyanine green lactosome) that is biocompatible and can be used for imaging cancer tissues and also as a drug delivery system. To date, stable particles are formed in blood and have an 10–20 h half-life. Particles labeled with a NIR fluorescent agent have been applied to cancer tissues by the enhanced permeability and retention effect in animals. Furthermore, this article reviews recent developments in photodynamic therapy with NIR fluorescence imaging, which may contribute and accelerate the innovative treatments for liver tumors.